2023
DOI: 10.3390/plants12051111
|View full text |Cite
|
Sign up to set email alerts
|

Maize Terpene Synthase 8 (ZmTPS8) Contributes to a Complex Blend of Fungal-Elicited Antibiotics

Abstract: In maize (Zea mays), fungal-elicited immune responses include the accumulation of terpene synthase (TPS) and cytochrome P450 monooxygenases (CYP) enzymes resulting in complex antibiotic arrays of sesquiterpenoids and diterpenoids, including α/β-selinene derivatives, zealexins, kauralexins and dolabralexins. To uncover additional antibiotic families, we conducted metabolic profiling of elicited stem tissues in mapping populations, which included B73 × M162W recombinant inbred lines and the Goodman diversity pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…Further analysis revealed that ZmTPS8 is a multiproduct α -copaene synthase. Its product, cubebol, exhibited significant antifungal activity against both Fusarium graminearum and Aspergillus parasiticus in vitro ( Saldivar et al., 2023 ). Otherwise, biosynthesis and emission of ( E , E )-α-farnesene triggered by caterpillars and aphids at a high density functioned as a phytochemical signal, attracting their natural enemies, Diadegma semiclausum parasitoids in Arabidopsis ( Kroes et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Further analysis revealed that ZmTPS8 is a multiproduct α -copaene synthase. Its product, cubebol, exhibited significant antifungal activity against both Fusarium graminearum and Aspergillus parasiticus in vitro ( Saldivar et al., 2023 ). Otherwise, biosynthesis and emission of ( E , E )-α-farnesene triggered by caterpillars and aphids at a high density functioned as a phytochemical signal, attracting their natural enemies, Diadegma semiclausum parasitoids in Arabidopsis ( Kroes et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%